Inferred immune-cell activity is an independent predictor of HER2-negative breast cancer prognosis and response to paclitaxel-based therapy in the GeparSepto trial - Fasching, Peter Andreas; Szeto, Christopher; Denkert, Carsten; Benz, Stephen; Weber, Karsten; Spilman, Patricia; Budczies, Jan; Schneeweiss, Andreas; Stickeler, Elmar; Schmatloch, Sabine; Jackisch, Christian; Karn, Thomas; et al. (Clinical cancer research, 2023)
Tumor microenvironment (TME) immune markers have been correlated with both response to neoadjuvant therapy and prognosis in patients with breast cancer. Here, immune-cell activity of breast cancer tumors was inferred by expression-based analysis to determine if it is prognostic and/or predictive of response to neoadjuvant paclitaxel-based therapy in the GeparSepto (G7) trial (NCT01583426).Pre-study biopsies from 279 patients with HER2-negative breast cancer in the G7 trial underwent RNA-seq-based profiling of 104 immune-cell-specific genes to assess inferred Immune Cell Activity (iICA) of 23 immune-cell types. Hierarchical clustering was used to classify tumors as iICA “hot,” “warm,” or “cold” by comparison of iICA in the G7 cohort relative to that of 1,467 samples from a tumor database established by Nantomics LLC. Correlations between iICA cluster, pathology-assessed tumor-infiltrating lymphocytes (TIL), and hormone receptor (HR) status for pathologic complete response (pCR), disease-free survival (DFS), and overall survival (OS) were determined.iICA cluster correlated with TIL levels. The highest pCR rates were observed in hot cluster tumors, and those with relatively higher TILs. Greater inferred activity of several T-cell types was significantly associated with pCR and survival. DFS and OS were prolonged in patients with hot or warm cluster tumors, the latter particularly for HR negative tumors, even if TILs were relatively low.Overall, TIL level better predicted pCR, but iICA cluster better predicted survival. Differences in associations between TILs, cluster, pCR, and survival were observed for HR-positive tumors versus HR-negative tumors, suggesting expanded study of the implication of these findings is warranted.